Pengaruh Brand Image dan Hedonistic Lifestyle terhadap Repurchase Intention Gen Z pada Starbucks Coffee - Yulia Natalia Elisabeth; Rezi Erdiansyah (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
The development of an increasingly modern era has made people's lifestyles change, one of which is the lifestyle factor that leads to a hedonic lifestyle by seeking pleasure in the form of glamorous life such as hanging out with friends in coffee shops. The